PENGARUH PROMOSI DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI TOKO HORE SANGATTA - Awaluddin, Muhammad (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
This study aims to examine the effect of promotion and price perception on purchasing decisions at Toko Hore Sangatta. In this research, the observed population consists of consumers at Toko Hore Sangatta, with a sample of 97 respondents selected to determine the influence of promotion, price perception, and purchasing decisions. Method: The method used in this study is a quantitative approach. Statistical analysis was conducted using SPSS version 24, applying multiple regression analysis to derive. Results: The findings indicate that both promotion and price perception have a positive and significant effect on purchasing decisions at Toko Hore Sangatta